Seismic isolation strategy via controlled soft first story with innovative multi-stage yielding damper: Experimental and numerical insights - Ghasemi, Sobhan; Hosseini, Mahmood; Hu, Shuling; Shahram, Amir (Elsevier Science Inc, 2024)
While the presence of a soft story within a building is typically discouraged in structural engineering due to potential vulnerabilities, this research proposes a strategy that incorporates seismic isolation concepts by integrating a soft first story within the structural framework. This approach challenges traditional reluctance by demonstrating the potential benefits of such a configuration. The primary objectives are twofold: firstly, to diminish seismic responses and enhance structural resilience when subjected to earthquake forces, and secondly, to reduce construction costs as compared to conventional passive control methods. The seismic responses assessed and compared in this study encompass story displacements, story drifts, floor accelerations and base shear of the structure. Furthermore, an investigation is conducted into a replaceable or repairable shear fuse that serves as a controller in the Controlled Soft First Story (CSFS) strategy, namely, an innovative Multi-stage Steel Yielding Damper (MSYD). Notably, the numerical analysis of the introduced damper has been carried out, followed by rigorous validation testing under experimental conditions. This study elucidates the implementation of this strategy within the structural framework. The overarching principle behind employing the CSFS results in outcomes akin to those achieved with base isolation techniques. However, it distinguishes itself by significantly mitigating the construction costs around 70% associated with this system when juxtaposed with traditional base isolation systems.
Keywords: Controlled soft first story; Seismic isolation; Multi-stage damper; Seismic resilience; Structural system; Experimental test; Cyclic behavior